2020
DOI: 10.1155/2020/3060475
|View full text |Cite
|
Sign up to set email alerts
|

Biological Pretreatment by Solid-State Fermentation of Oat Straw to Enhance Physical Quality of Pellets

Abstract: Pelleting can increase the efficiency of handling and transportation of biomass. Pretreatment obtains lignin fragments by disrupting the lignocellulosic structure of biomass and ensures the high-quality compressed pellets. In this study, solid-state fermentation (SSF) is used as a biological method to improve the quality of pellets of oat straw. SSF of oat straw using Trametes versicolor 52J (TV52J) and Phanerochaete chrysosporium (PC) was conducted. Response surface methodology (RSM) was employed by using a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…Gao et al [28] studied the physical quality of pellets from fungal-pretreated wheat straw and reported that fermentation temperature and time had significant effects on the pellet tensile strength and pellet unit density, which buttresses the findings of this present study. A significant effect of fermentation time on the tensile strength and unit density of pellets from TV52J-and PC-pretreated biomass was also recorded in similar studies by Gao et al [38] on oat straw and Gao et al [27] on corn stover. independent variables at a constant level.…”
Section: Effects Of Independent Variables and Their Interactions On The Switchgrass Pellet Qualitysupporting
confidence: 76%
See 1 more Smart Citation
“…Gao et al [28] studied the physical quality of pellets from fungal-pretreated wheat straw and reported that fermentation temperature and time had significant effects on the pellet tensile strength and pellet unit density, which buttresses the findings of this present study. A significant effect of fermentation time on the tensile strength and unit density of pellets from TV52J-and PC-pretreated biomass was also recorded in similar studies by Gao et al [38] on oat straw and Gao et al [27] on corn stover. independent variables at a constant level.…”
Section: Effects Of Independent Variables and Their Interactions On The Switchgrass Pellet Qualitysupporting
confidence: 76%
“…However, lower temperatures require longer fermentation times than the TV52J treatment at higher temperature. The optimum fermentation time reported in this study was in a close range with the optimum fermentation time obtained for the solid-state fermentation of oat straw using the same fungal strains [38]. Although the 21 d fermentation time reported in this present study is long relative to other pretreatment methods [43,44], it represents a significant reduction in fermentation time considering the 84 d of fermentation reported by Canam et al [22] and Kalinoski et al [23] using TV52J and the mutant strain (m4D).…”
Section: Optimization Of the Fungal Pretreatment For Fuel Pellet Productionsupporting
confidence: 73%
“…On the other hand, Fuel characteristics of oat straw pellets treated with Phanerochaete chrysosporium are as follows: density (immediate and after 14 days)-1108 kg/m 3 and 1068 kg/m 3 , Dimensional stability-1.14 %, Tensile strength-0.294 MPa for a fermentation duration and temperature of 35 days and 22 o C, with MC and particle size maintained as 70% and 50 mm, respectively. Overall, this study concluded that pre-treating biomass using microorganisms also helped in improvising the fuel characteristics, upon compaction (Gao et al, 2020).…”
Section: Oat Strawsmentioning
confidence: 72%
“…In another interesting study by Gao et al, 2020, oat straw were compacted into pellets, post treating it with fungal species namely: Trametes versicolor 52J and Phanerochaete chrysosporium. This study used Single pelleting unit operated at 4KN compaction pressure and produced pellets with dimension as follows: length-; diameter-.…”
Section: Oat Strawsmentioning
confidence: 99%
“…Solid-state fermentation represents a promising approach for the production of enzymes, as it offers the potential for recycling agro-industrial waste and simultaneously facilitates the delignification process, resulting in the generation of valuable products [27]. In this study, the fungal strain P. phaeocomes S-1 exhibited the ability to initiate the production of all three enzyme components of the enzyme cocktail within 24 h of incubation.…”
Section: Microorganismmentioning
confidence: 89%